2015
DOI: 10.31768/2312-8852.2015.37(3):192-196
|View full text |Cite
|
Sign up to set email alerts
|

Aconitine-Containing Agent Enhances Antitumor Activity of Dichloroacetate Against Ehrlich Carcinoma

Abstract: Significant variability of anticancer efficacy of dichloroacetate (DCA) stimulated an active search for the agents capable to enhance it antitumor action. Therefore, the aim of this work is the study of capability of aconitine-containing antiangiogenic agent BC1 to enhance anticancer activity of DCA against Ehrlich carcinoma. Materials and Methods: DCA (total dose was 1.3 g/kg of b.w.) and BC1 (total dose was 0.9 mg/kg of b.w.) were administered per os starting from the 2nd and 3rd days, respectively (8 admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Consequently, the Fe-S center of NADH dehydrogenase 3 from respiratory complex I is degraded, leading to significant suppression of mitochondrial respiration, which is at least partially responsible for PEITC anticancer activity. Also, combined treatment by dichloroacetate and aconitine-containing antiangiogenic agent BC1 proved significant antitumor activity against Ehrlich carcinoma [ 49 ]. Using this combination, substantial nitrosylation of Fe-S proteins was obtained.…”
Section: Fe-s Centers Are Targets Of Drug-induced Rosmentioning
confidence: 99%
“…Consequently, the Fe-S center of NADH dehydrogenase 3 from respiratory complex I is degraded, leading to significant suppression of mitochondrial respiration, which is at least partially responsible for PEITC anticancer activity. Also, combined treatment by dichloroacetate and aconitine-containing antiangiogenic agent BC1 proved significant antitumor activity against Ehrlich carcinoma [ 49 ]. Using this combination, substantial nitrosylation of Fe-S proteins was obtained.…”
Section: Fe-s Centers Are Targets Of Drug-induced Rosmentioning
confidence: 99%
“…Its application to disease conditions proved to exhibit an activity that slowed down cancer tumor growth and to cure serious cases of dermatosis. It was also found to have an effect on postoperative analgesia [ 9 , 10 , 11 , 12 ]. However, a previous safety study has revealed that aconitine toxicity is responsible for its restriction in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…A combined network analysis and in silico study was once performed to obtain insight on the relationship between aconitine alkaloid toxicity and the aconitine structure, and it was found that the cardiotoxicity of aconitine is the primary cause of patient death. The aconitine poison is similar to the poison created by some pivotal proteins such as the ryanodine receptor (RYR1 and RYR2), the Gap junction α-1 protein (GJA1), and the sodium–calcium exchanger (SLC8A1) [ 9 , 10 , 11 , 12 ]. However, among all existing studies about the aconitine medicinal, no one has reported detail of its specific binding target protein linked to toxicity.…”
Section: Introductionmentioning
confidence: 99%